From Compliance to Excellence: The TQM Story in Indonesian Health Service Providers - Firdaus, Rifani Hazhiyah; Irfan, Andi (Institut Bisnis dan Teknologi Pelita Indonesia, 2023)
The success in the industry manufacture has encouraged and motivated entity service health to implement TQM. Focus article This is to describe the development of TQM in Indonesia, especially in the healthcare industry. The evolution of TQM reflects a shifting paradigm in management quality from traditional control quality to more holistic, customer-centered, sustainable, and integrated with technology. This is an effort to reach more quality and improve the organization's overall performance. TQM is a sustainable approach in which the organization Keeps going continuously to increase quality and performance over time. This is not only for controlling quality but also about changing culture and practice organization for quality become a priority held close to everyone organization. Lack of support management, lack of involvement in employees, bad leadership, lack of training, culture organizations that do not appropriate, lack of recognition and award for success, and structure organization hierarchical and authoritative is the most obstacles quoted successful TQM implementation in developing countries. The evolution of TQM in The Worldwide Health Organization has become an essential thing for increasing the quality maintenance of health and satisfaction of patients.